Fracture resistance of computer‐aided design/computer‐aided manufacturing‐generated composite resin‐based molar crowns. (16th February 2015) - Harada, Akio; Nakamura, Keisuke; Kanno, Taro; Inagaki, Ryoichi; Örtengren, Ulf; Niwano, Yoshimi; Sasaki, Keiichi; Egusa, Hiroshi
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate whether different fabrication processes, such as the computer‐aided design/computer‐aided manufacturing (CAD/CAM) system or the manual build‐up technique, affect the fracture resistance of composite resin‐based crowns. Lava Ultimate (LU), Estenia C&B (EC&B), and lithium disilicate glass‐ceramic IPS e.max press (EMP) were used. Four types of molar crowns were fabricated: CAD/CAM‐generated composite resin‐based crowns (LU crowns); manually built‐up monolayer composite resin‐based crowns (EC&B‐monolayer crowns); manually built‐up layered composite resin‐based crowns (EC&B‐layered crowns); and EMP crowns. Each type of crown was cemented to dies and the fracture resistance was tested. EC&B‐layered crowns showed significantly lower fracture resistance compared with LU and EMP crowns, although there was no significant difference in flexural strength or fracture toughness between LU and EC&B materials. Micro‐computed tomography and fractographic analysis showed that decreased strength probably resulted from internal voids in the EC&B‐layered crowns introduced by the layering process. There was no significant difference in fracture resistance among LU, EC&B‐monolayer, and EMP crowns. Both types of composite resin‐based crowns showed fracture loads of >2000 N, which is higher than the molar bite force. Therefore, CAD/CAM‐generated crowns, without internal defects, may be applied to molar regions with sufficient fracture resistance.